The Latest Technologies in the Modular Credit Training System - N. M., Babakhodzhaeva (European Journal of Life Safety and Stability (2660-9630), 2021)
The article deals with the problems of using the latest technologies in a modular credit system. In particular, the methods of mastering the block of self-study by university students are analyzed. The author managed to develop new methods that develop communicative competence in students.